Anthony Burgess and reflections of Bangsa Malaysia: the liminal and liminoid identities in Beds in the East - Bahar, Ida Baizura; Abd Razak, Farahanna (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2017)
Beds in the east (1959), the third installment which forms part of The Malayan trilogy (1964), consisting also of Time for a tiger (1956) and The enemy in the blanket (1958), was written by the contemporary English author, Anthony Burgess (1917-1993) and is set in pre-independence Malaya. Exploring the themes of religion, ethnicity and nationhood, which are the main elements framing the lives of the Malayan society in its struggles towards independence, the trilogy was inspired by Burgess’ experiences living and working in Peninsular Malaya from 1954 to 1959, which in turn had shaped his perceptions and understandings of both countries, especially on the Malays’ practices of Islam and their culture. More importantly, Burgess actually predicted things in his novels by reflecting the present in order to project the future and this projection can be found in Beds in the east, which we hypothesise contains reflections of the current understanding of Bangsa Malaysia. In this paper, we explore the concept of Bangsa Malaysia by Tun Dr. Mahathir Mohamad (1991), as part of Malaysia’s Vision 2020, through Burgess’ portrayal of a Malay character, Syed Hassan, using the socio-anthropological approach of liminality. It comprises the liminal and liminoid phenomena as conceptualised by the British cultural anthropologist, Victor Witter Turner (1920-1989), which centralises on an identity of being betwixt and between. Findings of this paper demonstrate the liminal and liminoid conditions experienced by Syed Hassan to construct a balanced Malay identity which in turn do reflect the current understanding of Bangsa Malaysia.